2013
DOI: 10.1073/pnas.1222878110
|View full text |Cite
|
Sign up to set email alerts
|

Genomic responses in mouse models poorly mimic human inflammatory diseases

Abstract: A cornerstone of modern biomedical research is the use of mouse models to explore basic pathophysiological mechanisms, evaluate new therapeutic approaches, and make go or no-go decisions to carry new drug candidates forward into clinical trials. Systematic studies evaluating how well murine models mimic human inflammatory diseases are nonexistent. Here, we show that, although acute inflammatory stresses from different etiologies result in highly similar genomic responses in humans, the responses in correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
1,921
7
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,590 publications
(1,990 citation statements)
references
References 34 publications
33
1,921
7
5
Order By: Relevance
“…The first is that we studied post‐arrest metabolism in rats. The novel findings reported in this article may not be found in humans 61. We are currently conducting human studies to seek this newly found phenotype in survivors of CA.…”
Section: Discussionmentioning
confidence: 90%
“…The first is that we studied post‐arrest metabolism in rats. The novel findings reported in this article may not be found in humans 61. We are currently conducting human studies to seek this newly found phenotype in survivors of CA.…”
Section: Discussionmentioning
confidence: 90%
“…First, the sample size for the human cohort was small, and findings may not be generalizable to all women with PPD/A risk. Second, animal models, although extremely valuable for translational research in many instances, cannot always translate directly to clinical populations (Seok et al., 2013; Takao & Miyakawa, 2015). The model of a Western diet that we utilized enabled us to study the components of high fat and high BCAA separately and in interaction with each other to address our mechanistic hypothesis, but at the cost of including a high carbohydrate or high sugar component, which has also been implicated in a Western‐type diet.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the clinical prediction of pulmonary complications in trauma patients, both, understanding the underlying pathophysiology and the biology of the repair mechanisms as well as clinically reliable predictive biomarkers are necessary [46]. Moreover, improvement and development of translational trauma models are essential [47]. In the present study, we have evaluated the reliability of the clinically described biomarker LTB4 to indicate the risk for late lung injury and pulmonary complications in the long-term porcine severe polytrauma model.…”
Section: Discussionmentioning
confidence: 99%